2009
DOI: 10.1093/gerona/glp114
|View full text |Cite
|
Sign up to set email alerts
|

Driving Cessation and Health Trajectories in Older Adults

Abstract: The transition to driving cessation is associated with health declines for older adults as measured by several indicators. Additionally, general health declines more sharply following driving cessation. These findings highlight the importance of interventions to sustain driving mobility among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
199
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(212 citation statements)
references
References 24 publications
9
199
0
4
Order By: Relevance
“…While taking drivers with cataracts off the road might be a safe option, the negative consequences of losing one's driver licence include social isolation, decreased out of home activities, depressive symptoms and declines in health. [27][28][29] There were a significant proportion of the current drivers (31 per cent) and a greater proportion of the former drivers (54 per cent) who did not meet the Austroads guidelines for fitness to drive, although they may be eligible for a conditional licence after further assessment. 18 Keeffe and colleagues 30 reported only a small proportion of the general driving population failing this same criteria: 2.6 per cent had vision less than 6/ 12 in a sample of 1,787 current drivers aged 40 years and older in the Melbourne Vision Impairment Project (VIP).…”
Section: Discussionmentioning
confidence: 99%
“…While taking drivers with cataracts off the road might be a safe option, the negative consequences of losing one's driver licence include social isolation, decreased out of home activities, depressive symptoms and declines in health. [27][28][29] There were a significant proportion of the current drivers (31 per cent) and a greater proportion of the former drivers (54 per cent) who did not meet the Austroads guidelines for fitness to drive, although they may be eligible for a conditional licence after further assessment. 18 Keeffe and colleagues 30 reported only a small proportion of the general driving population failing this same criteria: 2.6 per cent had vision less than 6/ 12 in a sample of 1,787 current drivers aged 40 years and older in the Melbourne Vision Impairment Project (VIP).…”
Section: Discussionmentioning
confidence: 99%
“…Edwards et al (2009) indicated that driving cessation is associated with declines in physical and social functioning, as well as in general health (Edwards, Lunsman, Perkins, Rebok, & Roth, 2009). …”
Section: Mobility and Quality Of Lifementioning
confidence: 99%
“…This driving cessation could have negative consequences, such as social isolation or increased risk of depression [7][8][9][10]. However, older drivers can adapt their driving behavior to the age-related functional and cognitive decline by avoiding these difficult driving situations [11][12][13][14], or by developing compensatory strategies (e.g.…”
Section: Introductionmentioning
confidence: 99%